Enhancing Students’ Creativity through Product-Oriented Project-Based Learning with Teaching Aids in Straight Motion Kinematics - Ramadhani Aandrawina Ulpha; Hartono Hartono; Bambang Subali; Ani Rusilowati (Physics Communication, 2026)
This study aims to analyze the implementation of product-oriented project-based learning using instructional teaching aids to improve students’ creativity in learning the topic of straight motion kinematics. The aspects of creativity examined include fluency, flexibility, elaboration, and evaluation skills. This research employed an experimental method with a nonequivalent control group design. The research subjects consisted of an experimental class that applied product-oriented project-based learning using teaching aids and a control class that received conventional instruction. Data were collected through creativity tests and observation sheets. The results of the study indicate that the implementation of product-oriented project-based learning using teaching aids effectively improves students’ creativity. This improvement is demonstrated by the achievement of the creativity indicators, including fluency, flexibility, elaboration, and evaluation skills, in the experimental class compared to the control class. Therefore, product-oriented project-based learning using teaching aids can be considered an effective alternative instructional strategy to enhance students’ creativity in physics learning.